Construction of a wireless energy transmitter: Study by electromagnetic induction (Research, Society and Development, 2020)
The present work aims to show that it is possible to transmit electrical energy without the need for wires using coils that, by means of electromagnetic induction, allows the transmission of electrical energy wirelessly. This study is very useful because the technologies are becoming more compact, leading to the portability of some devices such as cell phones, notebooks, smartwatch, among others; and all of these devices need to be charged in a certain period, and the possibility of transmitting electric energy wirelessly would be a great resource to facilitate the life of users who need these devices for an extended time. In addition, we will verify the effectiveness of wireless energy, possible interferences in wireless energy transmission, and the physical phenomena present in the experiment. For the construction of the wireless energy transmitter, a bibliographic study and research on ways to transmit wireless energy were carried out, and the inductive coupling between two coils was chosen, which could use easily accessible materials, where the materials used were: Enamelled wire 0 , 7mm; 4 batteries of 1.5 Volts each; 1 KPS2222a transistor; 1 Led, 1 multimeter, 1 electrical tape. To understand the physical phenomena existing in the experiment, Halliday, Rennick (2016), Nussenzveig (1997), Feynman, Leighton and Sands (2008) were used. The research approach is qualitative, being of an experimental nature, and the data collected were collected through experiments. The results obtained allow us to understand the operation of wireless energy transmission in addition to verifying the possibility of transmitting electrical energy without the need for wire. The experiment carried out, in addition to contributing to research on wireless electrical energy transmission, has pedagogical contributions in the teaching process such as: 1. Defining the magnetic flux; 2. Verify that the variation of the magnetic flux can conduct an electric current, 3. Clarify Faraday's law: that the current induced in a closed circuit is proportional to the variation of the magnetic flux, 4. Verify that it is possible to induce alternating currents. These steps reveal the scope of the laboratory activity, being evident the importance of the experience in the area of Physics.